IDENTIFIKASI FITUR GUA MENGGUNAKAN TEKNOLOGI MULTI SENSOR (STUDI KASUS: GUA PAWON DAN GUA BARONG) - Rasendriya Nabil N., Muhammad
The Pawon Cave site and the surrounding caves are included in the area of ancient cultural heritage protected by the government. This site consists of several caves including the Pawon Cave and Barong Cave. The limestone exposed in this cave has a fragile nature and the cave's graffiti depicted on the rock is a factor that needs to be maintained in the context of this conservation. For this reason, it is necessary to document the condition of this cave, one of which is by utilizing the Terrestrial Laser Scanner (TLS) technology because it can accurately record objects. TLS is currently divided into two types, namely static and dynamic (handheld), therefore in this study, a comparison of the results of each type of TLS and also after they are both integrated will be carried out. In addition, cave graffiti will be assessed using static type TLS intensity data. The integration process between static and dynamic types of TLS is carried out using a cloud-to-cloud registration technique with the Natural Point Features method. The intensity value data processing from TLS statistics is carried out using the point cloud rasterization method, which is then calibrated for the intensity value. From the results of the comparison of the two types of TLS, it can be determined that the best method for recording cave features is the result of the integration of the two, especially the integration using Leica static TLS and Stonex brand TLS due to the smallest average recording error of 0.011 meters. Meanwhile, the intensity value on static TLS proved to be effective in exposing washed out cave streaks, especially on Leica brand static TLS because the streaks looked better visually than Trimble brand static TLS.